IL28B Gene Polymorphism SNP rs8099917 Genotype GG Is Associated with HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) in HTLV-1 Carriers - Assone, Tatiane; Souza, Fernando Vieira de; Gaester, Karen Oliveira; Fonseca, Luiz Augusto Marcondes; Luiz, Olinda do Carmo; Malta, Fernanda; Pinho, João Renato Rebello; Gonçalves, Fernanda de Toledo; Duarte, Alberto Jose da Silva; de Oliveira, Augusto Cesar Penalva; Casseb, Jorge (PLoS neglected tropical diseases, 2014)
The polymorphisms of IL28B have been described as important in the pathogenesis of infections caused by some viruses. The aim of this research was to evaluate whether IL28B gene polymorphisms (SNP rs8099917 and SNP rs12979860) are associated with HAM/TSP. The study included 229 subjects, classified according to their neurological status in two groups: Group I (136 asymptomatic HTLV-1 carriers) and Group II (93 HAM/TSP patients). The proviral loads were quantified, and the rs8099917 and rs12979860 SNPs in the region of IL28B-gene were analyzed by StepOnePlus Real-time PCR System. A multivariate model analysis, including gender, age, and HTLV-1 DNA proviral load, showed that IL28B polymorphisms were independently associated with HAM/TSP outcome in rs12979860 genotype CT (OR = 2.03; IC95% = 0.96-4.27) and in rs8099917 genotype GG (OR = 7.61; IC95%  = 1.82-31.72). Subjects with SNP rs8099917 genotype GG and rs12979618 genotype CT may present a distinct immune response against HTLV-1 infection. So, it seems reasonable to suggest that a search for IL28B polymorphisms should be performed for all HTLV-1-infected subjects in order to monitor their risk for disease development; however, since this is the first description of such finding in the literature, we should first replicate this study with more HTLV-1-infected persons to strengthen the evidence already provided by our results.